2022
DOI: 10.1016/j.ajoc.2022.101327
|View full text |Cite
|
Sign up to set email alerts
|

Late retinal and optic nerve vascular complications due to COVID-19 in young individuals

Abstract: Purpose This study aims to describe the late retinal and optic nerve vascular complications due Coronavirus disease 2019 (COVID-19) in a Spanish young population. Methods We describe 15 eyes of 15 young patients without any other systemic risk factors, except controlled arterial hypertension in 5 of them, with the diagnosis of Central retinal vein occlusion (CRVO), Branch retinal vein occlusion (BRVO), Central retinal artery occlusion (CRAO), Branch retinal artery occlu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…One of them spared the cilioretinal artery,[ 7 ] but this patient had a CRAO 4 months after COVID infection and had gone through minor symptoms, no hospitalization, and with previous COVID-19 infection confirmed by COVID-19 IgG test. [ 7 ] Our case developed CRAO with spared cilioretinal artery 11 days after discharge from hospitalization that required oxygen supplementation for severe COVID-19, had a positive RT-PCR for SARS-CoV-2 and several proinflammatory and procoagulant factors in her laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…One of them spared the cilioretinal artery,[ 7 ] but this patient had a CRAO 4 months after COVID infection and had gone through minor symptoms, no hospitalization, and with previous COVID-19 infection confirmed by COVID-19 IgG test. [ 7 ] Our case developed CRAO with spared cilioretinal artery 11 days after discharge from hospitalization that required oxygen supplementation for severe COVID-19, had a positive RT-PCR for SARS-CoV-2 and several proinflammatory and procoagulant factors in her laboratory tests.…”
Section: Discussionmentioning
confidence: 99%
“…Rho et al reported a 43-year-old male with underlying systemic diseases of diabetes mellitus and borderline hyperlipidemia presenting NAION two weeks after testing positive for SARS-CoV-2 by nasal swabbing [12]. Additionally, Larrea et al presented two cases of NAION after COVID-19 disease diagnosis, even though the 39-year-old female and 58-year-old male had no systemic risk factors for NAION [13]. These three patients all met the characteristics of minimal or no cardiovascular risk factors and experienced an early onset of NAION described by Kuhli-Hattenbach et al, and the authors argued that the hypoxemia and hypercoagulability caused by COVID-19 might contribute to the development of NAION [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Larrea et al presented two cases of NAION after COVID-19 disease diagnosis, even though the 39-year-old female and 58-year-old male had no systemic risk factors for NAION [13]. These three patients all met the characteristics of minimal or no cardiovascular risk factors and experienced an early onset of NAION described by Kuhli-Hattenbach et al, and the authors argued that the hypoxemia and hypercoagulability caused by COVID-19 might contribute to the development of NAION [12,13]. As compared with the above three cases, our patient also had minimal cardiovascular risk factors (controlled hypertension and borderline hyperlipidemia) despite developing NAION at an older age of 61 years, and the previous two reported cases of patients who experienced early-onset NAION (aged 46 and 55 years) also met the characteristics of no systemic risk factors described by Kuhli-Hattenbach et al [3,8].…”
Section: Discussionmentioning
confidence: 99%
“…12/100 required ventilatory support. Not reported OCT, FA RVO or RAO (n = 5) Uveitis (n = 3) CSCR (n = 2) Larrea et al 96 15 (M = 9, F = 6) 49.7 ± 9 Mild (n = 14) Moderate (n = 1) 3.70 ± 0.82 months OCT, OCTA CRVO (n = 6) CRAO (n = 4) BRAO (n = 1) CWS (n = 7) Macular edema (n = 8) Macular atrophy (n = 4) Retinal ischemia (n = 10) Bypareddy et al 97 138 (M = 94, F = 44) 38.51 ± 14.4 Mild to moderate Median 6 days (range 1–9 days) Fundus photos Retinal streak hemorrhage (n = 1) Zapata et al 98 96 (M = 34, F = 35) 41.3 No symptoms (n = 24) Moderate (n = 24) Severe (n = 21) Within 3 months of confirmed COVID-19 infection. OCT, OCTA Retinal hemorrhages (n = 1) Sim et al 99 108 COVID-19+ patients 36 ± 5.4 Mild Fundus exams were performed between 12 and 20 days after PCR diagnosis.…”
Section: Methodsmentioning
confidence: 99%